The postwar Columbia tradition in sociology: Its cognitive commonalities and social mechanisms - Crothers, Charles (Journal of classical sociology : JCS, 2024)
For a period of some three decades (1940s–1970s) the faculty and graduate students at the Department of Sociology at Columbia University, and its associated research unit (the Bureau of Applied Social Research: BASR), successfully produced a stream of innovative sociological studies which was particularly important in building on the foundations of classical sociology to establish modern sociology. Modern Sociology was produced as a theoretically sophisticated scientific enterprise firmly based on a solid empirical foundation produced by appropriate social research methods (as master-minded by Paul F. Lazarsfeld). The ‘Columbia Tradition’ is an approach, rather than being focussed on any particular subject matter, involved the development of ‘middle-range theory’, often broken-out from classic theory (as propounded by Robert K. Merton), and backed up by efforts at knowledge cumulation and institution building. But the School included a glittering array of important sociologists and hosts of others who extended the work of the two leaders, developing it in further directions, as is expected of any school. This school was sustained by the vision of a developing scientific sociology propounded by its founders, but it faltered as its founders retired from active leadership roles, in addition to being impacted by changes in Columbia University and broader Sociology environments.